Effect of injection layer sub-bandgap states on electron injection in organic light-emitting diodes - Hinzmann, Carsten; Hofstetter, Yvonne J.; Hopkinson, Paul E.; Vaynzof, Yana (ACS applied materials & interfaces, 2017)
It is generally considered that the injection of charges into an active layer of an organic light-emitting diode (OLED) is solely determined by the energetic injection barrier formed at the device interfaces. Here, we demonstrate that the density of surface states of the electron-injecting ZnO layer has a profound effect on both the charge injection and the overall performance of the OLED device. Introducing a dopant into ZnO reduces both the energy depth and density of surface states without altering the position of the energy levels - thus, the magnitude of the injection barrier formed at the organic/ZnO interface remains unchanged. Changes observed in the density of surface states result in an improved electron injection and enhanced luminescence of the device. We implemented a numerical simulation, modeling the effects of energetics and the density of surface states on the electron injection, demonstrating that both contributions should be considered when choosing the appropriate injection layer.